Biotization of the mediterranean stone pine (Pinus pinea L.) - Ragonezi, C. (2012)
In vitro mycorrhization of micropropagated plants can be used to resume the growth of the root system and to improve the acclimation phase by enhancing root functionality and improving the mineral and water status of the plants. To obtain these benefits an extensive characterization and identification of field ectomycorrhizas (ECM) that are associated with the target plant species is crucial. Not all fungi can promote in vitro rooting or other beneficial effects, hence it is necessary to test in co-culture each fungus–host plant–clone combination. To select effective clone–fungus interaction, the signals released by mycorrhizal symbionts, and how they influence the behavior of the partners have to be studied. In this context, we present the results of our four year-work on in vitro mycorrhization of Pinus pinea L. The effectiveness of inoculation of rooted plantlets, their survival rate as well as morpho-histological and physiological characterization are described in comparison with non inoculated plants during acclimation phase.